A WEB-BASED ENGLISH INSTRUCTION BLUEPRINT DESIGN: AN APPLICATION OF ESP WRITING COURSE - Risa Arroyyani; Lusi Nurhayati (English Review: Journal of English Education, 2021)
One among many considerations that should be taken into consideration when moving a conventional face-to-face course to a web-based course is learners' needs, which are transformed into a research-informed blueprint. This study addressed the process of blueprint design resulting from the needs analysis process of design-based research. The objective is to describe the designe   d blueprint set for a web-based English Writing course for nursing students in Indonesia. The blueprint consists of designs of learning approach, performance goals, learning tasks and feedback, instructional strategies, and web design modules and interface. The descriptive statistics were used to test 37 items scored by experts of ESP and Writing about the blueprint. The results of Expert Judgments showed that all items obtained mean at the ‘Good’ categories. It means that the blueprint can be used in conducting the next stage, which is website development.